The study of demonstration in motor learning: state of the art, challenges, and perspectives. DOI: 10.5007/1980-0037.2011v13n5p392 - Suzete Chiviacowsky; Flavio Henrique Bastos; Alessandro Teodoro Bruzi; Go Tani (Universidade Federal de Santa Catarina, 2011)
The aim of this study was to review the literature regarding demonstration as an important information source for the acquisition of motor skills. State of the art, main research challenges and some research perspectives are presented. Different theoretical bases have been used for the investigation of demonstration. The first is Bandura's social learning theory, in which proposals of how the observed information is processed by the learner are presented. Recent studies have tried to identify the nature of the observed information based on two theoretical models: motor and action approaches. Research findings based on Bandura's theory show that, during the process of observational learning, factors such as characteristics of the model, learner, demonstration, and motor skill differently affect the sub-processes related to the formation of the guide of action. On the other hand, studies investigating the nature of the information have shown advances in both theoretical approaches, but at a slower pace. For further developments to occur, we suggest a methodological exchange between the two theoretical approaches and investigations in which the learner has greater control over the request and use of demonstration.